Short-term effect of digital rectal examination on serum prostate-specific antigen levels - A prospective study - (:unkn) unknown (KARGER, 1996)
Objective: Prostate-specific antigen (PSA) is widely used as a tumor marker in the early detection of prostate cancer. However, its value is limited by several factors such as not being specific for the cancer tissue, diurnal variations of the secretion, and changes in the serum levels observed following rectal manipulations. The effect of digital rectal examination (DRE) on serum PSA levels is still debatable. Methods: A prospective study is conducted by utilizing the IRMA count (monoclonal) PSA assay in order to determine the effect of DRE on PSA serum levels. A total of 50 men (median age 61, range 42-75 years) who presented to our outpatient clinic for the first time with lower urinary tract outflow obstruction symptoms were included in this study. Further evaluation revealed prostate cancer in 5 patients(10%) and benign prostate hyperplasia in the others. Blood samples were drawn for a PSA assay from all patients prior to and 30 min and 24 h following DRE (PSA 1-3). Results: The mean PSA values prior to and 30 min and 24 h following DRE were 4.09 +/- 0.67 range 0.2-19.47) ng/ml, 4.50 +/- 0.63 (0.15-17.75), and 4.28 +/- 0.68 (0.23-24.12) ng/ml, respectively. The median PSA levels for PSA 1, PSA 2, and PSA 3 were 2.49 +/- 4.74, 3.22 +/- 4.48, and 2.62 +/- 4.82 ng/ml, respectively. Although, there was a statistically significant increase in serum PSA levels 30 min after DRE, the clinical significance of this increase in PSA values with a mean difference of 0.4 ng/ml remains to be clarified. Conclusion: Although the effect of DRE on PSA levels does not appear to be clinically significant, in order to prevent any confusion, it may be the best approach to perform DRE after obtaining serum for PSA analysis.
Keywords: digital rectal examination, serum prostate-specific antigen levels; prostate-specific antigen; tumor markers, prostate cancer; TUMOR-MARKER; ADENOCARCINOMA